A Comparison of Canadian and Japanese Cognitive Styles: Implications for Management Interaction - Abramson, Neil R.; Lane, Henry W.; Nagai, Hirohisa; Takagi, Haruo (Journal of International Business Studies, 1993)
Many American and Canadian companies seeking to form joint ventures and alliances with Japanese companies, or to negotiate contracts with them, have discovered that the interaction can be difficult and frustrating. Value differences and preferences for different management practices have been identified that contribute to these interaction problems. However, little research has investigated potential differences in cognitive style that might also contribute to intercultural conflict. This study compares samples of Canadian and Japanese MBA students using the Myers-Briggs Type Inventory (MBTI) and links the findings to interaction difficulties reported in the literature.